Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0478
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Clearance of Shrouded Rotor Blades on the Development of the Flowfield and Losses in the Subsequent Stator

Abstract: Although turbines are commonly noted for their high efficiency this efficiency can be improved further. The importance of the leakage flow for the losses of turbine stages makes this flow a promising candidate to be examined for loss reduction: first it decreases the workflow through the rotor and second, the suction side incidence of the re-entering leakage flow in the subsequent stator causes additional losses. As an essential parameter for leakage flow the clearance and its influence on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Only in recent years detailed measurement and computational fluid dynamics (CFD) simulations have been therefore performed focusing on the endwall cavity flows and on their influence on the main flow aerodynamic. Peters et al [3] evaluated the effects of the clearance of shrouded rotor blade on the downstream stator flowfield in a 1.5 axial turbine and found that the small turning angle in the labyrinth seal causes a negative incidence in the subsequent stator. Hunter and Manwaring [4] reported that the primary source of the losses associated with the cavities was the mixing of circumferential momentum components at the cavity exit.…”
Section: Introductionmentioning
confidence: 99%
“…Only in recent years detailed measurement and computational fluid dynamics (CFD) simulations have been therefore performed focusing on the endwall cavity flows and on their influence on the main flow aerodynamic. Peters et al [3] evaluated the effects of the clearance of shrouded rotor blade on the downstream stator flowfield in a 1.5 axial turbine and found that the small turning angle in the labyrinth seal causes a negative incidence in the subsequent stator. Hunter and Manwaring [4] reported that the primary source of the losses associated with the cavities was the mixing of circumferential momentum components at the cavity exit.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the earlier results have been presented in several publications, e.g. Peters et al [14], Giboni et al [15], and Anker and Mayer [16].…”
Section: Introductionmentioning
confidence: 78%
“…The CFD simulations of Anker & Mayer (2002) also underlined the importance of considering unsteady measurement and simulations to obtain a more realistic representation of these effects. Hunter & Manwaring (2000) and Peters et al (2000) showed that the size and location of the secondary flows are significantly affected by the interaction of labyrinth's leakage flow in turbines.…”
Section: Shrouded Tip Leakage Flow Interactionmentioning
confidence: 99%